2008
DOI: 10.1063/1.2876666
|View full text |Cite
|
Sign up to set email alerts
|

The effect of line-tying on tearing modes

Abstract: Cylindrical magnetohydrodynamic (MHD) constant-ψ or nonconstant-ψ tearing modes that are linearly unstable with periodic axial boundary conditions are studied in a line-tied cylinder. Examples of these two respective classes of modes, with m=1 and m=2 (m being the azimuthal mode number), are studied. With a suitable MHD equilibrium, the former modes are marginally stable in ideal MHD for periodic axial boundary conditions, and occur as fast tearing modes (resistive kinks) in the presence of resistivity η. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 17 publications
4
33
0
Order By: Relevance
“…Indeed, the modes for L → ϱ are tearing modes, and in Ref. 8 it was concluded that for long cylinder lengths the line-tied kink modes still behave as tearing modes, with growth rates proportional to the appropriate fractional power of resistivity. Close to marginal stability, on the other hand, the line-tied tearing modes evolve to global resistive diffusion modes, with ␥ ϰ .…”
Section: A Model: Full Visco-resistive Mhdmentioning
confidence: 98%
See 3 more Smart Citations
“…Indeed, the modes for L → ϱ are tearing modes, and in Ref. 8 it was concluded that for long cylinder lengths the line-tied kink modes still behave as tearing modes, with growth rates proportional to the appropriate fractional power of resistivity. Close to marginal stability, on the other hand, the line-tied tearing modes evolve to global resistive diffusion modes, with ␥ ϰ .…”
Section: A Model: Full Visco-resistive Mhdmentioning
confidence: 98%
“…Further, the threshold for this change occurs when the "geometric width" equals the tearing layer width. 8,9 The investigation of the stability of line-tied kink modes for equilibria 1-3 with axial flow allows one to explore the effects of the flow for the following relevant situations: ͑1͒ When the line-tied kink modes behave as either ideal modes or as tearing modes for long cylinder lengths and ͑2͒ when the modes behave as either ideal MHD modes or as resistive diffusion modes for short cylinder lengths close to marginal stability. In the next subsection, we briefly discuss the methods used for the stability analysis.…”
Section: A Model: Full Visco-resistive Mhdmentioning
confidence: 99%
See 2 more Smart Citations
“…Pritchett, Lee & Drake 1980;Ishii, Azumi & Kishimoto 2002;Bierwage et al 2005;Janvier, Kishimoto & Li 2011;Wang, Yokoyama & Isobe 2015). Finally the effect of line-tying, relevant in the context of coronal magnetic field, was investigated in Delzanno & Finn (2008), which found that the growth rate scaled with η for small structure lengths (compared with the system size), while it was tearing-like for long structures. This may be of interest considering different reconnecting coronal loops in the context of say, nanoflares involving small loops versus the larger structures generally seen in flares.…”
Section: Current Layer Formation and Evolutionmentioning
confidence: 99%